(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bamboo belongs low cost, fast growing and broad distribution of growth, is expected to contribute significantly in the developing countries we know from an ancient time bamboo is used as a construction material. The fact about cost optimization steel and bamboo is due to increasing cost of steel and there unavailability it is not possible for peoples to afford it bit by replacing steel as a bamboo we can easily move towards cost optimization. Bamboo is sustainable with steel because due to lack of knowledge regarding bamboo, there bonding and there physical and mechanical properties.no one can understand the fact that bamboo is as sustainable as steel to overcome the remedies of bamboo we have to improve their properties and there bonding strength with concrete for making bamboo as sustainable material as steel.